Sovereign risk premium and macroeconomy: Causal relationship - Maria Botey-Fullat; Cristina Marín-Palacios; Jesús Garcia Garcia-Doncel (Contemporary Economics, 2025)
In recent years, because of the 2008 financial crisis and the evolution of the sovereign debt markets, there has been a significant increase in interest in understanding the factors that determine the risk premium, becoming a key indicator of the financial stability of countries, and a measure of the risk assumed by investors who buy in a country's bonds or shares and for those responsible for the monetary policy. The aim of this study is to identify the possible causal relationships between the risk premium and various macroeconomic variables, as well as external factors that could influence its evolution. To do this, sources of economic-financial information based on monthly data covering the period from 2004 to 2022 are used. The methodology used focuses on the estimation of VAR (Autoregressive Vectors) models, which allows examining the dynamic interaction and causality between multiple variables. These models are suitable for studying the interdependence and mutual influence between the variables considered. The results obtained show that, although the risk premium has an autoregressive trend, there are other macroeconomic variables, such as the monetary aggregate M1, the bank default rate and the unemployment rate, which play a significant role in its behavior. Likewise, it is observed that external factors, such as the exchange rate or volatility index, also exert a significant influence on the risk premium.
Keywords: E43; E44; E62; G12; 330; risk premium; sovereign bond; fiscal policy; monetary policy; public indebtedness; VAR-model